Social policy in gender equality, empowerment and opportunities for women and girls in Vietnam (Revista de Investigaciones Universidad del Quindío, 2023)
Women have the right to be equal in all fields. This needs to be mainstreamed across the entire legal system, enshrined in both law and law enforcement, including positive measures such as quotas. As all areas of life are concerned with gender equality, efforts are needed to root out gender-based discrimination everywhere. Empowering women, and improving the status of women in society is a measure to accelerate the progress of countries towards achieving the goals of socially sustainable development. Vietnam is one of the countries that is always interested in women’s empowerment and gender equality in the process of sustainable development of the country. From the analysis of gender and feminist theories, the article will point out the motivating effects of women’s empowerment for socially sustainable development goals. Thereby, proposing solutions, contributing to the good implementation of women’s empowerment, and improving the status and role of women towards the goal of socially sustainable development in Vietnam now and in the future.
Keywords: Política social; igualdad de género; empoderamiento; las mujeres y las niñas; desarrollo sostenible; Vietnam